Pengaruh Pengaruh Price Earning Ratio (PER), Debt to Equity Ratio (DER), Net Profit Margin (NPM) dan Total Assets Turnover (TATO) Terhadap Harga Saham Pada PT. Unilever Indonesia Tbk Periode 2011 – 2018 - Witri Handayani; Elsya Meida Arif (Fakultas Ekonomi Universitas Borobudur, 2021)
The results showed that the variable Price Earning Ratio, Debt to Equity Ratio, Net ProfitMargin and Total Assets Turnover simultaneously had a positive and significant effect on stockprices with a Prob value (F-statistic) of 0.000032. Partially Price Earning Ratio has a positiveand significant effect with a t-statistic value of 5.621043 and a probability value of 0.0000, Debtto Equity Ratio partially has a positive and significant effect with a t-statistic value of 4.572382and a probability value of 0.0001. Net Profit Margin partially has a positive and significant effectwith a t-statistic value of 3.188182 and a probability value of 0.0036. Total Assets Turnoverpartially has a positive and significant effect with a t-statistic value of 4.611411 and a probabilityvalue of 0.0001. In addition, it is obtained that the adjusted R-squared value is 0.547148, thismeans that 54.77 stock price factors can be determined from the four independent variables.While the remaining 45.23 is influenced by other variables outside the study.Keywords: Price Earning Ratio, Debt to Equity Ratio, Net Profit Margin, Total Assets Turnover,Stock Price